The contemporary Scottish Gaelic linguistic and cultural landscape - Rogers, John Paul (Kansas State University, 2019)
Language is a key component of human culture that helps us define our world and communicate with others within it. Much like various aspects of material culture, the cultural landscape is rife with displays of the local language(s) and informs us of the values held by a people within a particular region. But what happens to this landscape when a language has fallen into disuse? In Scotland, the Gaelic language is one such example. Scottish Gaelic was dominant in the country, especially the Highland region, between the 10th and 16th centuries. The ascent of James VI of Scotland to the English throne, however, helped to spur the dominance of English in Scotland, with Gaelic falling out of favor as a result. Recent surveys by the Scottish Government have found that fewer than 100,000 speakers of Gaelic remain in Scotland, placing the language within the “endangered” category. What happens to the landscape of a language, in this case Scottish Gaelic, when the language has fallen out of dominance in its native region? Has the landscape of the Gaelic culture changed in the same way? In-depth field research in which elements of the cultural landscape (e.g. signs, shops, and events) were analyzed, aims to answer these questions and help us better understand the importance of and attitudes for a regional language within a culture as a whole.
Keywords: Scottish Gaelic; Cultural geography; Landscape analysis; Linguistic landscape